The Trouble with Disability in Shakespeare Studies - Wilson, Jeffrey R. (Disability Studies Quarterly, 2017)
This article reviews some instances of disability in Shakespeare's works and some instances of Disability Studies in Shakespeare studies. Contrary to the claims of the Disabled Shakespeares project, there is no historical basis for the modern language of "disability" in Shakespeare's texts, as illustrated with a philology of the term; this does not, however, invalidate the viable uses of disability theory in Shakespeare studies. Developing a typology of these uses (historical, methodological, critical, theoretical), this article discusses the opportunities and liabilities of each approach but concludes that a better vocabulary can be found in Erving Goffman's theory of stigma (which inspired Disability Studies but, in many ways, is more conceptually and ethically buoyant). The main goal in this article is not to argue against a Disability Studies approach to Shakespeare but, instead, to use those readings as evidence of the imperfect even if well-intentioned ways we respond to the encounter with stigma in Shakespeare's works – a phenomenon of literary criticism that is remarkably resonant with the similarly imperfect even if well-intentioned ways we respond to the encounter with stigma in our everyday lives.